Editorial: Tropical blue carbon: challenges and opportunities - Müller, Moritz (2025)
Blue carbon ecosystems - mangrove forests, seagrass meadows, and salt marshes - are essential for global organic carbon sequestration. These ecosystems serve as significant carbon sinks whilst contributing to climate change mitigation and adaptation. They provide numerous benefits, including coastal protection, water filtration, and nursery habitats (see Figure 1). However, these ecosystems are highly threatened by natural and anthropogenic stressors, with significant losses and degradation of habitats already observed. The vulnerability of these coastal ecosystems has been documented, and future climate-mitigation projects need to fully incorporate protection, restoration, and conservation of these important carbon sinks.